A Knight Without a Sword or a Toothless Tiger? The Effects of Audit Courts on Tax Morale in Switzerland - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
The intention of this paper is to analyse how audit courts affect tax morale, controlling in a multivariate analysis for a broad variety of potential factors. Switzerland with its variety of audit court competences among the cantons has been analysed. With data from the ISSP for 1999 evidence has been found that a higher audit court competence has a significantly positive effect on tax morale. Thus, the results in Switzerland suggest that in the cantons where audits courts are not just knights without swords or toothless tigers, they help improve taxpayers' tax morale and thus citizens' intrinsic motivation to pay taxes.
Keywords: H26; H73; D70; 330; Tax Morale; Tax Compliance; Tax Evasion; Audit Courts Direct Democracy; Local Autonomy